Troubling the Waters: Black African Christian Presence and the Reshaping of Christianity in Canada - Kwateng-Yeboah, James (Religion compass, 2026)
This article explores the histories of Christians of African descent in Canada, challenging Eurocentric narratives that have rendered their religious contributions invisible. Using polycentric framework, it examines how historic Black Christian communities—from Black Loyalists and Refugees in Nova Scotia to congregations across Ontario and Western Canada—transformed exclusion into religious innovation and institutional resilience. It then traces the post-1960s rise of African and Caribbean immigrant-initiated churches, demonstrating how transnational Pentecostal networks brought already-globalized expressions of Christianity to Canadian cities. The analysis reveals a shift from regional to global polycentricity. While earlier Black initiated churches indigenized Christianity within local conditions of struggle, contemporary African-initiated churches operate within worldwide webs of spiritual exchange. Despite remaining institutionally and epistemically marginalized, these communities function as agents of Christian revitalization. The article demonstrates that Christianity in contemporary Canada cannot be understood without accounting for the Black presence.